Data collection system in Latxa and Carranzana sheep breeding programme - Ugarte E.; Urarte E.; Arranz J.; Arrese F.; Gabiña D. (Data collection and definition of objectives in sheep and goat breeding programmes: New prospects, 1997)
The milk recording and selection programmes, developed in the Latxa and Carranzana breeds in the Basque Country and Navarre, in 1996 concerned 264 flocks with 85,692 ewes under milk recording, with 57 rams progeny tested and 11,728 Artificial Inseminations. Ewe and ram lambs selected for replacement are marked with a permanent non-electronic, plastic or metal, ear-tag and a tattoo. Data collection for reproductive performance and for milk recording is computerised in 57 per cent of the flocks, using programmed portable terminals. In the rest of the flocks, data collection is done by hand using forms printed on paper. A special computer programme has been developed in order to perform data collection for semen production and quality of rams of the Artificial Insemination Centre and to design the matings in order to reduce inbreeding and to optimise expected genetic gain.
Meeting of the FAO-CIHEAM Network of Cooperative Research on Sheep and Goats and Subnetwork on Animal Resources, 9-11 Mar 1997, Toulouse (France)